2002
DOI: 10.1097/00004770-200206000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Investigation of Second Mesiobuccal Canals in Endodontically Treated and Retreated Maxillary Molars

Abstract: An examination of 1873 conventionally treated and retreated maxillary first and second molars was made in an attempt to determine the percentage of second mesiobuccal (MB2) canals that could be located routinely and evaluate if there were any significant differences between initial treatments and retreatments. The teeth examined were 1193 first molars and 680 second molars treated consecutively over a 2-yr period by five endodontists. Overall the MB2 canal was found in 724 (61%) first molars and 245 (36%) seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
8

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(82 citation statements)
references
References 19 publications
1
69
0
8
Order By: Relevance
“…Inability to detect and cleaning of all canals and incorrect canal obturation are among the most important factors in treatment failure [2,12,13] . However, complete cleaning and shaping cannot be achieved because of root canal system complexity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inability to detect and cleaning of all canals and incorrect canal obturation are among the most important factors in treatment failure [2,12,13] . However, complete cleaning and shaping cannot be achieved because of root canal system complexity.…”
Section: Discussionmentioning
confidence: 99%
“…However, complete cleaning and shaping cannot be achieved because of root canal system complexity. It is difficult to measure the importance of these uncleansed areas in treatment success [13] .…”
Section: Discussionmentioning
confidence: 99%
“…5,6,[9][10][11] This occurrence must be investigated, since not observing a canal during endodontic therapy is a major cause of treatment failure. 7 According to the literature, [8][9][10][12][13][14][15][16][17] the observation of two canals in maxillary first molars ranges from 0 to 5.50%, and the observation of two independent foramens from 0 to 4%. On the contrary, there have been few studies focusing on the prevalence of this atypical occurrence in maxillary second molars, 14,16,18 although several case reports have been described.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Clinical studies confirm the presence of four root canals on maxillary first molars as the anatomical feature most frequently found. Wolcott et al 7 observed two canals in the mesiobuccal root in 61.1% of cases, and Buhrley et al 3 in 71.1%. In contrast to these findings, the frequency of reports of two palatal canals is low.…”
Section: Introductionmentioning
confidence: 95%
“…Wolcott, et al (45) found significant difference in the incidence of a MB2 canal between initial treatments and re-treatments suggests that failure to find and treat existing MB2 canals will decrease the long term prognosis. The incidence of a MB2 in first molar retreatments was 67% compared to a 59% incidence in initial treatments.…”
Section: Mesio-buccal Root Of Maxillary Molarsmentioning
confidence: 99%